Phonetic Reader Series-Shina - Rajapurohit, B.B. (My University, 1983)
This Phonetic Reader has six chapters excluding Introduction, Outline of Phonetics, Phonology of Shina, Phonetics of Shina, Pronunciation Drill, and Writing System.
Keywords: Shina